2021
DOI: 10.3390/molecules26103009
|View full text |Cite
|
Sign up to set email alerts
|

Aronia melanocarpa (Michx.) Elliot, Chaenomeles superba Lindl. and Cornus mas L. Leaf Extracts as Natural Preservatives for Pork Meat Products

Abstract: The aim of this study was to investigate the possibility of using Aronia melanocarpa, Chaenomeles superba, and Cornus mas leaf extracts as natural preservatives for pork meat products. Pork sausages were stored in modified atmosphere packaging (MAP) (80% N2 and 20% CO2) at 4 °C for 29 days. The total psychrotrophic counts (TPC) were determined during the storage period, along with the numbers of Enterobacteriaceae and lactic acid bacteria (LAB). The extracts improved the microbial quality of the meat products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The antimicrobial activity is not due to the total amount of polyphenols but to the chemical composition of the extracts [36]. Numerous flavonoids: flavan-3-ols, flavonols and tannins were identified in the extract of Cistus incanus we studied.…”
Section: Antibacterial Activity Of C Incanus Extract and Dyesmentioning
confidence: 83%
See 1 more Smart Citation
“…The antimicrobial activity is not due to the total amount of polyphenols but to the chemical composition of the extracts [36]. Numerous flavonoids: flavan-3-ols, flavonols and tannins were identified in the extract of Cistus incanus we studied.…”
Section: Antibacterial Activity Of C Incanus Extract and Dyesmentioning
confidence: 83%
“…As in our study, they observed slowing of lipid oxidation processes and inhibited deterioration. Efenberger-Szmechtyk et al [36] observed that the addition of leaf extracts of A. melanocarpa, C. superba, and C. mas to pork sausages stored in MAP inhibited lipid oxidation. The C. superba extract had the greatest effect on the MDA concentration in the sausages.…”
Section: Effect Of Polyphenolic Extract and Dyes On Lipid Oxidation In Pork Sausagesmentioning
confidence: 99%
“…Previously, Photobacterium was found to be relatively abundant in pork stored under air or vacuum and may play a greater role in meat spoilage than previously thought [52]. Previous studies have also shown that Photobacterium require a complex medium with a high NaCl content for growth, and even the use of a standard medium such as PCA was not sufficient to culture the isolates, although high-throughput sequencing revealed Photobacterium as the predominant microflora in pork sausages [53]. However, the same authors found that the relative abundance of Photobacterium decreased during storage, which was also the case in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Efenberger-Szmechtyk et.al. used Aronia melanocarpa as a natural preservative in pork products [ 58 ].…”
Section: Synthetic Vs Natural Antioxidants In the Food Industrymentioning
confidence: 99%